2017
DOI: 10.1021/acsbiomaterials.7b00673
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Polarity of Mussel-Inspired Adhesives in the Realization of Strong Underwater Bonding

Abstract: Although the role of 3,4-dihydroxyphenyl-L-alanine­(DOPA)­in mussel foot proteins (mfps) in the realization of underwater bonding has been widely recognized, the role of the polarity of the polymer was largely overlooked. Here, by systematically comparing the underwater bonding properties of four mussel-inspired adhesives with different amide/lactam contents but similar catechol contents and molecular weights, we came to the conclusion that the polarity of the polymers also contributes to the strong underwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
2
42
0
2
Order By: Relevance
“…They did, however, find a correlation between the adhesion force and the ratio of cationic to hydrophobic residues in the remainder of the peptide. This is in agreement with the work of Mu et al [27], who investigated the influence of polymer backbone polarity on catechol adhesion by introducing a catecholic moiety at ≈20% of the monomers in polystyrene, poly(acrylate-co-acrylamide), polyacrylamide, and poly( N -vinylpyrrolidone), and comparing wet (seawater) and dry adhesion using a lap-shear test (Figure 3d) on aluminum, glass, and polytetraflourethylen substrates. They found that the bonding strength increased with increasing polarity of the backbone polymer, demonstrating the importance of the chemical environment for catechol adhesion.…”
Section: Catechol Chemistrysupporting
confidence: 90%
See 1 more Smart Citation
“…They did, however, find a correlation between the adhesion force and the ratio of cationic to hydrophobic residues in the remainder of the peptide. This is in agreement with the work of Mu et al [27], who investigated the influence of polymer backbone polarity on catechol adhesion by introducing a catecholic moiety at ≈20% of the monomers in polystyrene, poly(acrylate-co-acrylamide), polyacrylamide, and poly( N -vinylpyrrolidone), and comparing wet (seawater) and dry adhesion using a lap-shear test (Figure 3d) on aluminum, glass, and polytetraflourethylen substrates. They found that the bonding strength increased with increasing polarity of the backbone polymer, demonstrating the importance of the chemical environment for catechol adhesion.…”
Section: Catechol Chemistrysupporting
confidence: 90%
“…The diverse chemistry of catechols is summarized in Scheme 1. Strong, yet reversible, and very pH-dependent coordination bonds establish strong adhesion to inorganic surfaces (metals and metal oxides) [1,24,25,26,27] (Scheme 1f,g) as well as hard metal ions in solution [6,28,29,30,31,32,33,34] (Scheme 1c). Similarly, catechols can participate in boronate species (Scheme 1d) that are reversible, even if they possess a high degree of covalency [35,36,37,38].…”
Section: Catechol Chemistrymentioning
confidence: 99%
“…[ 17 ] White and Wilker [ 18 ] and Joy and co‐workers [ 19,20 ] incorporated monomers with electrostatic charges or aliphatic pendants into CFPs, achieving underwater bonding strength of 0.4 MPa on aluminum and 0.65 MPa on glass, respectively. By adjusting the polarity [ 21 ] or the hydrophilicity [ 22 ] of CFP backbones, Wan et al reported improved bonding strength of 1.13 and 1.33 MPa on glass substrates. Waite and co‐workers constructed complex coacervates by incorporating polycation with catechol‐functionalized polyanion, which also achieved robust underwater adhesion.…”
Section: Methodsmentioning
confidence: 99%
“…So zeigte eine Studie über die Polarität der Hauptkette eines synthetischen Polymers mit Catechol‐Einheiten eine zusätzliche Komplikationsquelle, da die Polarität spezifische Eigenschaften des Polymers, z. B. die Unterwasseradhäsion, verändert . Andere Untersuchungen an redoxaktiven catecholhaltigen Polymeren ergaben, dass die Veränderung des catecholhaltigen Monomers sowie des Comonomers das Leistungsverhalten bei der elektrochemischen Energiespeicherung beeinflussen kann .…”
Section: Phenolische Bausteineunclassified